2003
DOI: 10.1081/jcmr-120022258
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Changes in Myocardial Relaxation Using Three-Dimensional Tagged Magnetic Resonance Imaging

Abstract: Tagged MRI is a unique, noninvasive imaging method that can identify significant prolongation and reduction of myocardial relaxation in older compared with young normal individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
54
2
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(69 citation statements)
references
References 26 publications
12
54
2
1
Order By: Relevance
“…24 However, LV twist increases with advancing age, probably because of subendocardial dysfunction. 9,21,25 The early diastolic release of increased potential energy stored during this augmented systolic twisting deformation may be the cause of the preserved peak diastolic untwisting velocity and untwisting rate with ageing found both in the current study and by Takeuchi et al 9 Our findings of strong, age-independent relationships between LV peak systolic twist and peak diastolic untwisting velocity and untwisting rate support this hypothesis. Nevertheless, although the peak diastolic untwisting velocity and untwisting rate did not change significantly, with advancing age both parameters were impaired when normalized for the increased extent of LV twist.…”
Section: Influence Of Ageing On LV Untwistingsupporting
confidence: 81%
“…24 However, LV twist increases with advancing age, probably because of subendocardial dysfunction. 9,21,25 The early diastolic release of increased potential energy stored during this augmented systolic twisting deformation may be the cause of the preserved peak diastolic untwisting velocity and untwisting rate with ageing found both in the current study and by Takeuchi et al 9 Our findings of strong, age-independent relationships between LV peak systolic twist and peak diastolic untwisting velocity and untwisting rate support this hypothesis. Nevertheless, although the peak diastolic untwisting velocity and untwisting rate did not change significantly, with advancing age both parameters were impaired when normalized for the increased extent of LV twist.…”
Section: Influence Of Ageing On LV Untwistingsupporting
confidence: 81%
“…The sample size of each group was relatively small (8 to 10 subjects), although the characteristics of LV torsional deformation were clearly demonstrated. LV torsional deformation in elderly people has previously been reported 24 but was not a focus of the present study, although such future data would be very interesting. Detailed examination of LV mechanics by tissue-tagged magnetic resonance imaging showed that infant myocardial angular deformation is not homogeneous in any given short-axis LV plane, 35 although some of this variability may reflect measurement noise.…”
Section: Limitationsmentioning
confidence: 62%
“…Higher fiber stress is associated with enhanced torsion, and in general, fiber stress rises with age in adults, predicting that there should be an age-related rise in torsion. Oxenham et al 24 reported that peak apical rotation and LV torsion were increased in older subjects (69 years) more so than in younger ones (22 years). Our results suggest that LV torsion increases even earlier, as shown in our middle-aged adults (averaging 42 years).…”
Section: Enhanced Lvtor N In Infancy and Middle-age Adultsmentioning
confidence: 99%
“…This indicates a potential subendocardial dysfunction, which is further associated with reduction in longitudinal shortening observed with physiological aging and hypertrophic cardiomyopathy. 6,7,9 Previous studies also demonstrated a decline in cardiac high-energy phosphate (PCr/ATP ratio) in older individuals. 9,10 This may be because of multiple reasons, such as altered creatine content or the activity of creatine kinase which we cannot determine from these data.…”
Section: Discussionmentioning
confidence: 99%